Socio demographic and clinical profile of dengue fever cases at a tertiary care hospital, Hyderabad, Telangana - Chajhlana, Sunil Pal singh; Mahabhasyam, Ramakrishna Narashimha; Varaprasada, Maruti Sarma Mannava; Reddy Anukolu, Ravi Shankar (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue fever is caused by Dengue Virus, belonging to the family Flaviviridae, transmitted by Aedes aegypti and Aedes albopictus mosquito. There are four distinct dengue virus serotypes (DEN-1, DEN-2, DEN-3, and DEN-4). This viral disease of humans has become a major international public health concern in recent years. Differential diagnosis based on symptoms is challenging due to dengue’s non-specific symptoms such as fever, aches and fatigue that are often overlap with other endemic infections. Dengue-associated mortality can be reduced from 20–30% in severe cases to less than 1% with appropriate fluid replacement and supportive care, which is greatly facilitated by early diagnosis. Aim and objective: To study the demographic factors and clinical features of dengue fever cases in urban areas of Hyderabad. Methods: The present study was conducted by Department of Community Medicine in collaboration with Department of Microbiology, Kamineni academy of medical sciences and research center, Hyderabad. Study subjects: “Probable” dengue cases admitted in the various departments during July –December 2016. Data collection was done using a structured questionnaire. Serum samples were tested for NS1 antigen, IgM, IgG antibodies by rapid visual immunochromatography. Results: Out of 137 samples of clinically suspected dengue cases, 119 were found positive for dengue infection. Fever was the most common symptom found in all the patients Majority of cases, 56.3% were males. Thrombocytopenia, leucopenia and bleeding manifestation were found in 84.0 %, 84.8% and 58.8% patients respectively. Conclusions: Fever was the most common symptom found in all the patients. Majority of cases showed thrombocytopenia. Significant difference was found in the clinical signs and symptoms like fever, myalgia, hypotension, thrombocytopenia and leucopenia in dengue cases than controls.